Frequency, predictors and outcomes of intradialytic complications in patients on maintenance haemodialysis in Dar es Salaam: Prospective longitudinal study - John Robert Dugilo; Fatma Bakshi; Muzdalifat Abeid; Samina Somji (PLoS ONE, 2025)
Introduction Hemodialysis is a crucial renal replacement therapy option for end stage renal disease (ESRD) patients. Currently, there is a rise of patients who require hemodialysis with concurrent rise in intradialytic complications which can potentiate several outcomes some of which are life threatening. This study assessed the frequency, predictors, and outcomes of intradialytic complications amongst ESRD patients on maintenance hemodialysis. Methodology Prospective longitudinal study using self-designed questionnaires including patient’s demographic data and relevant past medical history, pre-hemodialysis assessment and intra-dialysis monitoring was done for 2 months at Aga Khan Hospital and Muhimbili National Hospital, in Dar es salaam, Tanzania. Results 215 patients were enrolled, of which 138(64.2%) were males with mean age 57(SD 15.37), height 1.64(SD 0.08) and weight 69.27(SD 12.62). Most patients 197(91.6%), were on thrice weekly schedule of which the duration of each session in most patients 206(95.8%) was 4 hours. Diabetes mellitus was the most common etiology of ESRD 126 (58.6%), ArterioVenous fistula (AVF) was the most common vascular access for the procedure 90(41.9%) and mostly, high flux dialyzers were used, FX100 & FX80, (211, 98.2%). There was a statistically significant association between pre-dialysis vital signs, blood flow rate and sex (p value <  0.05) with intradialytic hypertension and hypotension. Interestingly, male sex appeared to elicit a protective effect on intradialytic hypotension (p value < 0.001). Conclusion Hemodialysis is a life-saving procedure with multiple complications of which some have detrimental outcomes. Nonetheless, having a good understanding of the factors associated with the complications, appropriate management and ways of preventing them will remarkably improve the procedure and make it a safer renal replacement modality. Carefully, monitoring pre-dialysis vitals and taking necessary measures when deranged, individualized proper machine settings, sufficient fluid removal and standard blood flow rate may improve the dialysis procedure.